Pengaruh Model Pembelajaran Problem Solving Terhadap Kemampuan Berfikir Kritis, Motivasi Belajar, dan Hasil Belajar Ekonomi Siswa Kelas X SMAN 1 Masbagik - Muspita, Zalia; Sholihah, Isfi (Universitas Hamzanwadi, 2019)
The purpose of this study was to determine the effect of simultaneous model of problemsolving on critical thinking skills, motivation and learning outcomes of Economic studies students of the sevent grade at Senior high school number 1 Masbagik - East Lombok. This study is a quasi-experimental. Data were collected with the critical thinking skills tests, questionnaires, and tests student learning outcomes. Overall the data and hypothesis testing is done using Manova analysis.Based on the above results, the conclusion can be formulated as follows: (1) In a partial implementation of the model problem solving have a relationship with the critical thinking skills of Economi students in the sevent grade at Senior high school number 1 Masbagik - East Lombok. (2) In a partial implementation of the model-solving have relationship problems with the sevent grade at Senior high school number 1 Masbagik - East Lombok. (3) In a partial implementation of the model-solving have relationship problems with motivation to learn in the sevent grade at Senior high school number 1 Masbagik - East Lombok. (4) In the simultaneous application of problemsolving models have a relationship with the students' critical thinking skills, motivation and learning outcomes of social studies students in the sevent grade at Senior high school number 1 Masbagik - East Lombok.